(untitled) (Sustainability in Debate, 2016)
Environmental concern has generated interest in research about new materials aligned with the principles of sustainability. Currently, among these materials are the composites made from renewable resources. This article presents the results of a case study about products containing the mentioned composites. A search was performed on the World Wide Web, using the Google search engine, about products made with these composites. They were compared with products made from materials commonly used in industry, such as polymers, metals and ceramics. It was found that composites made from renewable sources are used mainly in packages and in the production of gardening tools and plant pots. The finding is that such composites can replace commonly used materials, meeting functional and aesthetic requirements of industrial producers.